1912
DOI: 10.1098/rsta.1912.0009
|View full text |Cite
|
Sign up to set email alerts
|

IX. Memoir on the theory of the partitions of numbers. - Part VI. Partitions in two-dimensional space, to which is added an adumbration of the theory of the partitions in three-dimensional space

Abstract: I Resume the subject of Part V. of this Memoir by inquiring further into the generating function of the partitions of a number when the parts are placed at the nodes of an incomplete lattice, viz., of a lattice which is regular but made up of unequal rows. Such a lattice is the graph of the line partition of a number. In Part V. I arrived at the expression of the generating function in respect of a two- row lattice when the past magnitude is unrestricted. This was given in Art. 16 in the form GF ( ∞ ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Finally, taking the limit m, n → ∞ of (14) gives rise to the classical MacMahon generating series [17]:…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, taking the limit m, n → ∞ of (14) gives rise to the classical MacMahon generating series [17]:…”
Section: 4mentioning
confidence: 99%
“…For our purposes, the left hand side is interpreted as a formal generating series for plane partitions with base contained in an m × n rectangle. The right hand side is then the partition function (a many parameter generalization of MacMahon's formula [17]). The Schur polynomials s λ have a one-parameter t-generalization in the Hall-Littlewood polynomials P λ (Chapter III of [16]).…”
Section: Introductionmentioning
confidence: 99%
“…This lemma, in combination with (13) and (11), implies that | Q(e −dn+iθ ) |= o(Q(e −dn )/ b(e −dn )) uniformly for δ n ≤| θ |≤ π, which is just Hayman's "decay" condition.…”
Section: Proof Of Theoremmentioning
confidence: 94%
“…Plane partitions are originally introduced by Young [27] as a natural generalization of integer partitions in the plane. The problem of enumerating plane partitions was studied first by MacMahon [13] (see also [14]), who showed that, for any parallelepiped B(l, s, t) = {(h, j, k) ∈ N 3 : h ≤ l, j ≤ s, k ≤ t} and any | x |< 1, ∆⊂B(l,s,t)…”
Section: Introductionmentioning
confidence: 99%